DEFECT PRODUCT COMPARISON OF THE USE OF ALCOHOL-BASED FOUNTAIN SOLUTION AND ALCOHOL-FREE IN OFFSET PRINTING - Mawan Nugraha; Murdani Murdani (Kreator, 2020)
One of the main components of the fountain solution used for the offset printing technique is isoprophil alcohol (IPA), which is related to its function as a surface tension reducing agent, cooling agent for printing plates and at the same time having anti-bioorganic function. However, complaints have also been made about the weaknesses in the use of IPA related to odor, toxicity and too high evaporation rate during its use. Therefore, in this article, IPA is compared to the "alcohol-free" type when used in the field as a wetting solution mixture using a KBK offset printing machine to produce magazines using of AP 115 paper. The difference in the use of the two surfaces the tension reducing agents are identified by the waste parameters that are used, generated during consistent printing under controlled process conditions. The results obtained indicate that the use of IPA is always higher, but the use of `` non alcoholic '' tends to be more stable in controling the process.Keywords—Isoprophil Alcohol (IPA), alcohol-free fontain solution, offset printing